2009
DOI: 10.1111/j.1445-5994.2008.01696.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and management of hypertension in patients with type 2 diabetes

Abstract: The DEMAND and NEFRON studies both show that BP control is achievable in Australian general practice, with more than half of all patients seeing their general practitioners achieving a target systolic BP < or =130 mmHg. However, more needs to be done to further reduce BP levels, particularly in patients at high risk of adverse outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…As per previous research, the frequency of hypertension was high among the patients and higher among those who had an uncontrolled HbA 1c level 26,30,31. The prevalence of retinopathy and heart diseases as comorbidities among our DM patients was less than the previous local study 32.…”
Section: Discussionsupporting
confidence: 65%
“…As per previous research, the frequency of hypertension was high among the patients and higher among those who had an uncontrolled HbA 1c level 26,30,31. The prevalence of retinopathy and heart diseases as comorbidities among our DM patients was less than the previous local study 32.…”
Section: Discussionsupporting
confidence: 65%
“…Interestingly, this association was similar in patients with higher and lower SBP during follow-up and was directly comparable to the 18% reduction in the risk for cardiovascular disease for every halving of albuminuria rates reported from the Reduction in Endpoints in Noninsulin dependent diabetes mellitus with the Angiotensin II Antagonist Losartan (RENAAL) study. 35 In that study, discordant responses between albuminuria and BP were observed in a significant proportion of individuals, adding more support for albuminuria as a therapeutic target in addition to BP in patients with type 2 diabetes; however, both the analyses from RENAAL and this study are observational and should therefore be regarded as primarily exploratory.…”
Section: Subgroups Of Follow-up Egfr Levelsmentioning
confidence: 74%
“… Notes: a Data of interest = incidence or prevalence of hypertension and/or obesity among adults with T2DM (searches one and two) or risk association of hypertension/obesity with long-term micro- or macrovascular complications of T2DM (search one only); b does not exclude patients hospitalized with T2DM complications; c publication types excluded were commentaries, case studies, interim reports when end-of-study data were available, and reviews for which primary data were already included; d one article (Thomas and Atkins29) reported on two studies, for a total of 78 studies in 77 articles.…”
Section: Figurementioning
confidence: 99%
“…Mid-range values are not shown in the figure. a Mean ages in the study by Hassing et al59 were 83.1–84.0 years; b Suh et al76 provided both low and high estimates; c Thomas and Atkins29 provided both low and high estimates (two studies in one report); d the low estimate in South America used an atypical definition of hypertension (the proportion of patients with systolic blood pressure >144 mmHg) 82…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation